Three decades of Indian power-sector reform:A critical assessment. (February 2021) - Ghosh, Santosh; Yadav, Vinod Kumar; Mukherjee, Vivekananda; Gupta, Shubham
Abstract: The accumulated financial loss of the Indian state-owned electricity utilities (SOEUs) has crossed over USD 6.25 billion and 80% of the SOEUs are consistently incurring losses and hence financially unsustainable in long term. In this article, the impact of three decades of Indian policy reform towards reviving the techno-commercial performance of the SOEUs is critically assessed. To quantify the relative performance of SOEUs and bring out the reason behind the inefficiencies of individual SOEUs, data envelopment analysis improved by Shannon's entropy model is applied. The benchmark SOEUs are identified for each inefficient ones, and corrective policy measures are recommended. Highlights: Presents a chronology of the evolution of the Indian power-sector policy framework. Techno-commercial performance of the Indian power sector is critically analyzed. DEA Models improved by Shannon's entropy is applied for comparative analysis. Applied methodology improved the discrimination capability of DEA models. Defacto impact of power sector reform strategies evaluated & alternatives proposed.